2007
DOI: 10.1111/j.1365-2567.2007.02606.x
|View full text |Cite
|
Sign up to set email alerts
|

A paracrine role for chemoattractant receptor‐homologous molecule expressed on T helper type 2 cells (CRTH2) in mediating chemotactic activation of CRTH2+ CD4+ T helper type 2 lymphocytes

Abstract: Activation of human CRTH2(+) CD4(+) T helper type 2 (Th2) cells with anti-CD3/anti-CD28 led to time-dependent production of prostaglandin D(2) (PGD(2)) which peaked at 8 hr. The production of PGD(2) was completely inhibited by cotreatment with the cyclo-oxygenase inhibitor diclofenac (10 microm) but was not affected by cotreatment with ramatroban, a dual antagonist of both the thromboxane-like prostanoid (TP) receptor and the chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2). Supernat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 47 publications
(62 reference statements)
2
19
0
1
Order By: Relevance
“…P rostaglandin D 2 is the major prostanoid released from mast cells (1) and is also produced in substantial quantities by Th2 lymphocytes (2,3). It has been detected in high concentrations at sites of allergic inflammation and mediates its effects through high affinity interactions with D prostanoid receptor (DP) 2 1 (2) and chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2; also named DP 2 ).…”
Section: Novel Function Of Crth2 In Preventing Apoptosis Of Human Th2mentioning
confidence: 99%
See 1 more Smart Citation
“…P rostaglandin D 2 is the major prostanoid released from mast cells (1) and is also produced in substantial quantities by Th2 lymphocytes (2,3). It has been detected in high concentrations at sites of allergic inflammation and mediates its effects through high affinity interactions with D prostanoid receptor (DP) 2 1 (2) and chemoattractant receptor-homologous molecule expressed on Th2 cells (CRTH2; also named DP 2 ).…”
Section: Novel Function Of Crth2 In Preventing Apoptosis Of Human Th2mentioning
confidence: 99%
“…ϩ CD4 ϩ Th2 cells were prepared using a modified method described previously (3). Briefly, PBMC were isolated from buffy coats from healthy blood donors whose atopic status was unknown (National Blood Service, Bristol, U.K.) by Ficoll Hypaque (Amersham Biosciences) density gradient centrifugation, followed by CD4 ϩ cell purification using MACS CD4 ϩ T cell isolation kit II (Miltenyi Biotec).…”
Section: Human Crth2mentioning
confidence: 99%
“…It has been reported that activated Th2 cells are able to produce PGD 2 (7,8). To understand whether the enhancing effect of cysLTs is mediated by a secondary production of PGD 2 by Th2 cells, we examined the effect of diclofenac, a cyclooxygenase inhibitor, on cytokine production induced by LTE 4 (Fig.…”
Section: Lte 4 Does Not Affect Pgd 2 Production and Crth2 Expression mentioning
confidence: 99%
“…PGD 2 , produced by the activity of the cyclooxygenase enzymes, is the major prostanoid released from mast cells during an allergic response (3,4), although macrophages (5), dendritic cells (6), and CD4 + Th2 lymphocytes (7,8) may contribute to PGD 2 production in some circumstances. A significant contribution of PGD 2 to the development of allergic inflammation has been suggested by the observations of enhanced eosinophilic lung inflammation and cytokine release in transgenic mice overexpressing PGD 2 synthase (9).…”
mentioning
confidence: 99%
“…P rostaglandin (PG) D 2 is a product of arachidonic acid metabolism that is secreted predominantly by mast cells [1] but also by T-helper cell (Th) type 2 lymphocytes [2]. Levels of PGD 2 are raised in the airways of patients with asthma after allergen challenge [3], suggesting a role for this prostanoid in promoting Th2-mediated allergic inflammation.…”
mentioning
confidence: 99%